Patient engagement in a Canadian health research funding institute: implementation and impact - Dawn P Richards; Karim Khan; Rosie Twomey; Trudy Flynn; Linda Hunter; Eunice Lui; Allan Stordy; Christine Thomas (BMJ Open)
Background Patient engagement (PE) or involvement in research is when patient partners are integrated onto teams and initiatives (not participants in research). A number of health research funding organisations have PE frameworks or rubrics but we are unaware of them applying and reporting on their own internal PE efforts. We describe our work at the Canadian Institutes of Health Research’s Institute of Musculoskeletal Health and Arthritis (CIHR IMHA) to implement, evaluate and understand the impact of its internal PE strategy.Methods A co-production model was used involving patient partners, a PE specialist and staff from IMHA. A logic model was co-developed to guide implementing and evaluating IMHA’s PE strategy. Some of evaluating the PE strategy and understanding its impact was a collaboration between the Public and Patient Engagement Collaborative (McMaster University) and IMHA.Results IMHA convened a PE Research Ambassador (PERA) group which co-led this work with the support of a PE specialist. In doing so, PERA had a number of meetings since 2020, set its own priorities and co-produced a number of outputs (video, publications, webinars, blog and modules called the How-to Guide for PE in Research). This work to evaluate and measure impacts of IMHA’s PE strategy revealed positive results, for example, on PERA members, Institute Advisory Board members and staff, as well as beyond the institute based on uptake and use of the modules. Areas for improvement are mainly related to increasing the diversity of PERA and to improving accessibility of the PE outputs (more languages and formats).Conclusions Implementing a PE strategy within CIHR IMHA resulted in several PE activities and outputs with impacts within and beyond the institute. We provide templates and outputs related to this work that may inform the efforts of other health research funding organisations. We encourage health research funders to move beyond encouraging or requiring PE in funded projects to fully ‘walk the talk’ of PE by implementing and evaluating their own PE strategies.